Preparation of scented teas by sustained-release of aroma from essential oils–casein nanocomposites. (July 2021) - Xu, Longjie; Li, Kexin; Xv, Liuli; Zhang, Haihua; Zhang, Yahui; Liu, Xv; Xu, Yongquan; Yin, Junfeng; Qin, Dingkui; Jin, Peng; Du, Qizhen
Abstract: The traditional scenting process is complicated and limited by the short flower season. In this study, formulated jasmine essential oil-casein nanoparticles (JEO–CS–NPs) were prepared for scenting green tea, in this case, Huangshan Maofeng. The freeze-dried JEO–CS–NPs (FD-JEO–CS–NPs) with a JEO/CS ratio of 0.25 encapsulated more than 70% of the JEO, and the JEO could be sustainably released for 60 days. After being scented by placing FD-JEO–CS–NPs in the tea package for 50–60 days at room temperature, the tea leaves effectively adsorbed and retained the aromatic compounds and presented a favorable smell of jasmine fragrance with good aroma maintenance. This could be ascribed to the sustained-release of aromatic compounds from the FD-JEO–CS–NPs. The new technology also avoided destroying the color of the soaked tea liquid and infused leaf since the scenting process is performed in the tea package using the antioxidative jasmine essential oil. The research showed that the new scenting technology can be extensively applied for the production of tea leaves scented with various flower fragrances. Graphical abstract: Image 1 Highlights: Jasmine essential oil-casein nanoparticle was formulated for scenting tea. Freeze-dried nanoparticle presents sustained-release of aromas in 60 days. Scented tea by nanoparticle gave favorite and sustaining smell of jasmine fragrance. This technology helps to protect the color of soaked tea liquid and infused leaf.